2017
DOI: 10.1111/cote.12325
|View full text |Cite
|
Sign up to set email alerts
|

The study of imidazoles Gemini surfactants as retarders for the dyeing of cationic dyes on polyacrylonitrile fabrics

Abstract: Alkyl imidazole cationic Gemini surfactants (AICGS) with various alkyl chain lengths were used as retarders for dyeing methylene blue (MB) on polyacrylonitrile (PAN) fabrics, with benzyldimethyldodecylammonium chloride (1227) surfactant as a comparison. The exhaustion (E%) of MB on PAN fabrics was investigated at varying surfactant concentrations and dyeing temperatures. Furthermore, kinetic studies on various retarders and 10‐4‐10 AICGS concentrations were carried out. It was found that the retarding dyeing e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Cao et al reported that dye in surfactant micelle showed decreased absorption properties. 31 On the other hand, both MB and C 12 -MB showed the similar absorption at 293 nm, which indicated that long hydrocarbon chain was not graed to the nitrogen atoms of phenothiazine. From uorescence emission spectra in Fig.…”
Section: Photophysical Propertiesmentioning
confidence: 96%
“…Cao et al reported that dye in surfactant micelle showed decreased absorption properties. 31 On the other hand, both MB and C 12 -MB showed the similar absorption at 293 nm, which indicated that long hydrocarbon chain was not graed to the nitrogen atoms of phenothiazine. From uorescence emission spectra in Fig.…”
Section: Photophysical Propertiesmentioning
confidence: 96%
“…Indigo blue was successfully synthesized in 1880 and was imported into China at the beginning of the twentieth century [13]. Because indirubin was a by-product in early synthetic indigo [62,63], both plant-based and synthetic indigo could be used in this waistcoat.…”
Section: Dyesmentioning
confidence: 99%
“…Synthetic dyes were introduced to China in the late nineteenth century and soon occupied a major Fig. 1 main distribution area of the Gyalrong Tibetan people (drawn according to [5,6], the yellow star marks the location of Danba County where the waistcoat was collected) market share, because they were less expensive, more readily available than natural dyes and not affected by seasons [13]. By the end of the nineteenth century, methods had been developed to modify and dissolve cellulose from cotton and wood pulp, and to extrude the solution to produce "artificial silk".…”
Section: Introductionmentioning
confidence: 99%
“…In addition, negatively charged third monomers such as carboxyl and sulfonic groups have been added during the commercial processing of PAN fiber to improve its dyeing performance. 31 Due to the electrostatic repulsion between the PAN fiber and GO, GO adsorption on the fiber surface is difficult. Only a few studies have focused on the modification of PAN fiber with the aim of improving the GO adsorption of the fiber.…”
mentioning
confidence: 99%